(untitled) (European journal of volunteering and community-based projects, 2024)
This article investigates whether and how a "business-like" approach is associated with the evolution of philanthropy over time in a sample of Italian banking foundations (FOB). Data were collected through a questionnaire addressed to the chairpersons and administrators of the banking foundations in two distinct periods, five years apart. The results show a positive and significant correlation between the implementation of planning and control tools and a broader adoption of strategic philanthropy as perceived by top-level individuals within the foundations. Furthermore, administrators who bring specific managerial skills and are offered training at the time of their appointment are more likely to perceive improvements in philanthropic action. Additional analyses reveal that as the composition of governance changes (especially when replacing the chairperson), the association between planning and control systems and strategic philanthropy becomes negative, thus confirming the strong leadership role played by the chairperson within the FOBs.